Examining trade flow dynamics in the face of deglobalization and decoupling: A comparative analysis of developing and developed nations - Imran-Ur-Rahman, ,; Shafi, Mohsin; Muhammad Ashraf, Fauzi; Fetuu, Enitilina Tatiani M.K. (Emerald Publishing, 2024)
This article examines the concepts of “deglobalization” and “decoupling” from the perspectives of developing and developed nations. It also assesses the short-term impacts of globalization, particularly in the context of the COVID-19 pandemic and predicts the long-term effects on global trade and cooperation between nations. Design/methodology/approach: Panel data from 85 countries (2000–2022) were utilized. Poisson Pseudo-Maximum Likelihood (PPML) regression analysis was conducted to analyze pre- and post-COVID-19 globalization levels. The analysis focuses on trade patterns and trends, specifically comparing the effects on developing and developed nations. Findings: First, there was a slight decline in global trade in 2020 due to COVID-19, followed by recovery in 2021–2022. Second, developing nations experienced more significant trade declines than did developed nations. Third, while US? China trade decreased slightly, China-India and US-India trade increased during the pandemic. These findings suggest that while there may be short-term disruptions, long-term trends indicate resilience in global trade patterns, with shifts in output and new partnerships emerging. Originality/value: This study contributes to the understanding of deglobalization and decoupling by providing empirical evidence on pre- and post-COVID-19 trade patterns. The findings suggest that while globalization may have short-term effects, it is likely to lead to post-pandemic recovery and strengthened cooperation between developing and developed nations. This research also highlights the importance of developing strategies to manage uncertainty and external shocks in global trade, emphasizing the role of lockdown measures, national security considerations, and trade policies in shaping the future of globalization and decoupling.